D4 receptor activation differentially modulates hippocampal basal and apical dendritic synapses in freely moving mice - Li, Shi-Bin; Koehr, Georg (Cerebral cortex, 2016)
Activation of D4 receptors (D4Rs) has been shown to improve cognitive performance, potentially affecting synaptic strength. We investigated the D4R agonist PD 168077 (PD) in hippocampal CA1 of freely moving mice. We electrically stimulated in stratum oriens (OR) or radiatum (RAD) and evoked local field potentials (LFPs). Intraperitoneally injected PD dose-dependently and reversibly attenuated LFPs for longer time in basal (OR) than apical (RAD) dendrites. High-frequency stimulation induced LTP that was stronger and more stable in OR than RAD. LTP lasted at least 4 h during which the paired-pulse ratio remained reduced. A PD concentration not affecting synaptic transmission was sufficient to reduce LTP in OR but not in RAD. A PD concentration reducing synaptic transmission reduced the early phase LTP in OR additionally and the late phase LTP in RAD exclusively. Furthermore, cell type-specific expression of mCherry in DATCre mice generated fluorescence in dorsal CA1 that was highest in lacunosum moleculare and similar in OR/RAD, indicating that midbrain dopaminergic fibers distribute evenly in OR/RAD. Together, the D4R-mediated modulation of hippocampal synaptic transmission and plasticity is stronger in OR than RAD. This could affect information processing in CA1 neurons, since signals arriving via basal and apical afferents are distinct.